PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS XI SMK - Eliyati Viranda; Metrilitna br Sembiring; Dhia Octariani; Isnaini Halimah Rambe (Universitas Islam Sumatera Utara, 2022)
This study aims to: 1). Determine the level of validity, the effectiveness, and practicality of student worksheets developed with the learning model problem-based learning class XI in SMK, 2). Find out increase the learning interest of the students of class XI SMK after using students' worksheets with the model of problem-based learning. The research type used is Research and Development refers to model 4-D, namely define, design, develop, and disseminate. However, in this study, the research development worksheet using problem-based learning is modified bounded only at the stage of development. Subjects in this study were students of class XI business management of SMK Budi Utomo Cikampak. Instruments of assessment used are a validity questionnaire, a test of interest in learning, and a student responses questionnaire. The results obtained that the worksheet has been developed to meet the criteria of validity with an average score of 4.2 in the valid category. Mastery learning in the classical style has been experiencing an increase in trial I (59,09%) in trial II increased by (90,90%) with the learning time does not exceed the usual learning, the student worksheet has been effective. Student Worksheet has been developed to meet the criteria of practicality review of the questionnaire responses of students to the shows that the average score 81,76% with the strong category. (2) the learning Interest of students has increased, namely with an average increase from the pretest to the posttest with a score increase of 80.5% with a high category.